KRITERIA VISIBILITAS HILAL DALAM PENETAPAN AWAL BULAN KAMARIAH DI INDONESIA - Suhardiman, Suhardiman (Khatulistiwa, 2013)
To determine the start of lunar months, there are several methods that serve as the basis, among others by using the methods of hisab (calculation) and rukyat (new moon sighting). Actually, both hisab and rukyat have the same goal, namely hilal. Therefore, the two methods do not need to be disputed any more. In fact they complement each other. Calculation of the correct and accurate reckoning will certainly be proven by rukyat anyway. However, the problem remain for Muslims today is the critera imkan ar-rukyat (visibility of the new moon) used. If these problems can be overcome, then it is certain that Muslims are no longer stuck with the difference of opinions and views from many quarters about the determination of the beginning of the month, when the hilal is on a "critical" position. As for the criterion concerning the visibility of the new moon in Indonesia, which has been used by the Government and become standard in the determination of kamariah (Ramadhān, Syawāl and Dzulhijjah) is the height of hilal at 2 degrees, the Sun-Moon distance is a minimum of 3 degrees, or a minimum hilal period of 8 hours based on data collected by the Agency of Hisab and Rukyat of the Ministry of Religious Affairs from a variety of sources. This is an implementation of the legitimate law (the Qur'an and the Hadith) that serves as the basis in determining the beginning of the month. In addition, the validity of rukyat is first tested with astronomical data which are discussed in the next session of the forum and later in Isbat decided by the Government and becomes an alternative solution to the differences of opinion and views that may occur. The Government through the Minister of Religious Affairs serves as the holder of authority (qadi) which has the legal authority to determine the beginning of the Islamic fasting and holy day in isbāt session held annually. Through Ditjen Bimas Islam, the Agency of Hisab and Rukyat (BHR) was established which is in charge of conducting the study, research and development of matters relating to the implementation of the hisab-rukyat and worship. Therefore, Muslims also need to support the realization of an Islamic calendar (Hijri calendar), which gives the certainty of dates, not only used for the purpose of worship, but can also be used as a civil calendar for everyday purposes, such as trade, business and other administrative activities.